First-line chemotherapy in low-risk gestational trophoblastic neoplasia - Alazzam, Mo’iad (2012)
BACKGROUND: This is an update of a Cochrane review that was first published in Issue 1, 2009. Gestational trophoblastic neoplasia (GTN) is a rare but curable disease arising in the fetal chorion during pregnancy. Most women with low-risk GTN will be cured by evacuation of the uterus with or without single-agent chemotherapy. However, chemotherapy regimens vary between treatment centres worldwide and the comparable benefits and risks of these different regimens are unclear. OBJECTIVES: To determine the efficacy and safety of first-line chemotherapy in the treatment of low-risk GTN. SEARCH METHODS: In September 2008, we electronically searched the Cochrane Gynaecological Cancer Group Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL Issue 3, 2008), MEDLINE and EMBASE. In addition, we searched online trial registers, conference proceedings and reference lists of identified studies. We re-ran these searches in February 2012 for this updated review. SELECTION CRITERIA: For the original review, we included randomised controlled trials (RCTs), quasi-RCTs and non-RCTs that compared first-line chemotherapy for the treatment of low-risk GTN. For this updated version of the review, we included only RCTs. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed studies for inclusion and extracted data to a pre-designed data extraction form. Meta-analysis was performed by pooling the risk ratio (RR) of individual trials. MAIN RESULTS: We included five moderate to high quality RCTs (517 women) in the updated review. These studies all compared methotrexate with dactinomycin. Three studies compared weekly intramuscular (IM) methotrexate with bi-weekly pulsed intravenous (IV) dactinomycin (393 women), one study compared five-day IM methotrexate with bi-weekly pulsed IV dactinomycin (75 women) and one study compared eight-day IM methotrexate-folinic acid (MTX-FA) with five-day IV dactinomycin (49 women). Overall, dactinomycin was associated with significantly higher rates of primary cure than methotrexate (five studies, 513 women; RR 0.64, 95% Confidence Interval (CI) 0.54 to 0.76). Methotrexate was associated with significantly more treatment failure than dactinomycin (five studies, 513 women; RR 3.81, 95% CI 1.64 to 8.86). We consider this evidence to be of a moderate quality. There was no significant difference between the two groups with respect to nausea (four studies, 466 women; RR 0.61, 95% CI 0.29 to 1.26) or any of the other individual side-effects reported, although data for all of these outcomes were insufficient and too heterogeneous to be conclusive. No severe adverse effects (SAEs) occurred in either group in three out of the five included studies and there was no significant difference in SAEs between the groups overall (five studies, 515 women; RR 0.35, 95% CI 0.08 to 1.66; I(2) = 60%), however, there was a trend towards fewer SAEs in the methotrexate group. We considered this evidence to be of a low quality due to substantial heterogeneity and low consistency in the occurrence/reporting of SAEs between trials. AUTHORS’ CONCLUSIONS: Dactinomycin is more likely to achieve a primary cure in women with low-risk GTN, and less likely to result in treatment failure, compared with methotrexate. There is limited evidence relating to side-effects, however, the pulsed dactinomycin regimen does not appear to be associated with significantly more side-effects than the low-dose methotrexate regimen and therefore should compare favourably to the five- and eight-day methotrexate regimens in this regard. We consider pulsed dactinomycin to have a better cure rate than, and a side-effect profile at least equivalent to, methotrexate when used for first-line treatment of low-risk GTN. Data from a large ongoing trial of pulsed dactinomycin compared with five- and eight-day methotrexate regimens is likely to have an important impact on our confidence in these findings.